EFFICACY OF NIGERIAN GROWN Erythrophleum suaveolens (Gull. And Perr.) Brenan BARK EXTRACTS AS BIOPRESERVATIVE AGAINST TERMITE ATTACK: Received: 28th July 2021; Revised: 30th November 2021, 17th January 2022, 30th January 2022; Accepted: 31st January 2022 - Owofadeju, F.K. (MATTER: International Journal of Science and Technology, 2022)
Many synthetic chemicals that are used to protect wood from biodeterioration are associated with environmental pollution and toxicity to human beings. As a part of the search for less hazardous preservatives, extracts from the bark of Erythrophleum suaveolens were evaluated using ethanol extraction process. Samples of barks of Erythrophleum suaveolens were obtained from Oyo town, Nigeria. Phytochemical and elemental analyses were carried out on the oil extracts. Permeability and decay resistance tests were carried out on lumber samples of Ceiba pentandra in accordance with ASTM standards. Results were analyzed using Analysis of Variance (ANOVA) at 5% probability level. Phytochemical analysis indicated the presence of Saponin (13.56%), Tannin (29.71mg/g), alkaloid (6.39%) and Total Phenol (38.71mg/g) while elemental analysis showed the presence of Copper, Iron, Lead, Magnesium and Calcium respectively. Grave yard Test showed that the untreated Ceiba pentandra samples had the highest weight loss after 6 weeks of exposure while 100% treatment had least weight loss. The oil extract from bark of Erythrophleum suaveolens was effective against termite attack on Ceiba pentandra wood samples and therefore has good potentials as biological preservative for wood and other lignocellulosic materials.